Great peacemakers: true stories from around the world - Beller, Ken; Chase, Heather (Sedona, Ariz. : LTS Press, 2008)
Profiles twenty people who have promoted peace in their lives from a Vietnamese monk to a Brazilian musician. Explores five approaches to peacemaking: choosing nonviolence, living peace, honoring diversity, valuing all life, and caring for the planet.
Keywords: Pacifists--Biography--Juvenile literature; Civil rights of workers--Biography--Juvenile literature; Animal rights activists--Biography--Juvenile literature